Secular Trends of Acute Viral Hepatitis Incidence and Mortality in China, 1990 to 2019 and Its Prediction to 2030: The Global Burden of Disease Study 2019 - Su, Xing; Zheng, Lin; Zhang, Huami; Shen, Ting; Liu, Yingna; Hu, Xiaowei (Frontiers in Medicine, 2022)
Background: Understanding the patterns and trends in the context of both incidence and mortality and anticipating future trends is important for viral hepatitis prevention, treatment, and guiding resource allocation in China. The objective of this study is to provide a comprehensive temporal analysis of acute viral hepatitis and its type using the most updated data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD 2019) to estimate the incidence and mortality of hepatitis from 1990 to 2019 and make predictions to 2030. Methods: The age-standardized incidence (ASIR) and mortality rate (ASMR) of viral hepatitis in China were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD 2019). Trends of ASIR and ASMR for viral hepatitis were plotted using locally weighted regression (LOESS). We used joinpoint regression analysis to detect temporal changes and estimate the annual percent of change (APC) of each trend segment and the corresponding 95% confidence interval (CI). A Bayesian age-period-cohort analysis was employed to describe ASIR and ASMR trends between 1990 and 2019 and projections to 2030. Results: In 1990, there were 67 million incident cases of acute viral hepatitis, which then decreased to 47 million incidence cases in 2019. Hepatitis A and hepatitis B account for the majority of acute viral hepatitis, and the most pronounced declines in hepatitis B (-48.7%) and hepatitis C (-39.0%) were observed between 1990 and 2019. The ASIR of overall acute viral hepatitis shows a persistent decline, with an average annual percent of change (AAPC) of -1.9% (95% CI: -1.9, -1.8) between 1990 and 2019. The trend of ASMR demonstrated a rapid decline between 1990 and 2005, followed by a slow decline until 2030. Conclusions: Our study reveals favorable declining trends of incidence and mortality for acute viral hepatitis in China from 1990 and 2019, and these favorable trends are predicted to continue up to 2030. Despite the favorable trends observed, the absolute number of viral hepatitis, especially hepatitis A and B, is still substantial in China. A scaled-up vaccine campaign is still needed to tackle the large number of vaccine preventable hepatitis infections.